2012
DOI: 10.1117/12.930090
|View full text |Cite
|
Sign up to set email alerts
|

Toward active x-ray telescopes II

Abstract: In the half century since the initial discovery of an astronomical (non-solar) x-ray source, the observation time required to achieve a given sensitivity has decreased by eight orders of magnitude. Largely responsible for this dramatic progress has been the refinement of the (grazing-incidence) focusing x-ray telescope, culminating with the exquisite subarcsecond imaging performance of the Chandra X-ray Observatory. The future of x-ray astronomy relies upon the development of x-ray telescopes with larger apert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…For this reason, the method can be useful for a sensitive mirror shape diagnostics under X-rays, without the need to remove the mirror from the vacuum chamber to re-measure its profile. For this reason, this approach can be very useful in active X-ray optics applications 21 to derive the mirror shape directly under X-rays, and consequently provide a feedback to the actuator matrix and optimize the mirror shape in real time.…”
Section: Conclusion and Expected Angular Resolutionmentioning
confidence: 99%
“…For this reason, the method can be useful for a sensitive mirror shape diagnostics under X-rays, without the need to remove the mirror from the vacuum chamber to re-measure its profile. For this reason, this approach can be very useful in active X-ray optics applications 21 to derive the mirror shape directly under X-rays, and consequently provide a feedback to the actuator matrix and optimize the mirror shape in real time.…”
Section: Conclusion and Expected Angular Resolutionmentioning
confidence: 99%
“…The angular resolution of the Chandra -type imaging system is mainly determined by the degree of the surface smoothness and alignment accuracy of the mirrors, which are achieved only through costly high-precision manufacturing. Given the enormous cost in manufacturing the Chandra mirrors (estimated to be several hundred million dollars 3 ), it is unfeasible to further improve the angular resolution from that of Chandra , or even to match it, with similar methods.…”
Section: Introductionmentioning
confidence: 99%
“…At MSFC, we are involved in several technology development efforts for higher resolution, larger area, and lighter weight x-ray optics to support future replacement of the 15-year-old Chandra X-ray Observatory, [1][2][3][4] with the next mission to attain sub-arcsecond x-ray imaging. All of these technologies [5][6][7][8][9][10][11][12][13][14][15] share the need to be mounted, assembled, and aligned into modular units for testing or for flight. Because in our recent experience with moderate-resolution optics [16][17][18][19][20] we have found that without considerable development effort, it is difficult to prevent structure induced errors from contributing significantly, i.e.…”
Section: Introductionmentioning
confidence: 99%